Hydrodynamic Simulation of Suspended Solids Concentration in Isahaya Regulating Reservoir: DOI: 10.32526/ennrj.18.2.2020.20 - Khiem Ta, Cong; Suzuki, Seiji; Huy Nguyen, Nhat (Environment and Natural Resources Journal, 2020)
In this study, Osaka daigaku estuary model (ODEM) was applied for hydrodynamic simulation of suspended solids (SS) concentration in the Isahaya regulating reservoir. Water samples were collected every hour from 9:00 to 15:00 at nine sampling points inside the observation area of the reservoir. Parameters used for the model included initial conditions (i.e., SS concentration, water depth, temperature, and salinity) and boundary conditions (i.e., wind speed and direction, atmospheric temperature, solar irradiation, and cloud cover). The calculated results of SS in the reservoir and its concentration fluctuation from the model were compared with those estimated from the image analysis of unmanned aerial vehicle (UAV) and observed results. The SS simulated from ODEM distributed in high concentration, whereas that estimated from UAV distributed in low concentration although in both data they spread across a wide range at most investigated times. Although there was a big difference between the accuracy of ODEM and UAV, the SS concentration values described by them were closed to the observed values. Between them, the ODEM model showed its advantages in simulating the SS concentration and achieved more accuracy than UAV, showing a potential for using ODEM model in monitoring of SS in water.